The Irish fairy tale : a narrative tradition from the Middle Ages to Yeats and Stephens - Carrassi, Vito (John Cabot University Press : Distributed by University Of Delaware Press in partnership with the Rowman & Littlefield Pub. Group, 2012)
Through an original analysis of its structure and dynamics, the fairy tale ceases to be one of the many genres of fantastic narrative and rises to become a category, a universal modality both of the storytelling and of a world vision. The objective is to render the fairy tale a sort of emblematic location, where the study of narrative texts integrates itself with the socio-historical contexts of the Irish tradition.